L’église Saint-Martin de Savigny du xie au xviiie siècle. - Olivia Puel (Archéologie Médiévale)
The abbey of Savigny (Rhône) was a mighty ecclesiastical seigneury which occupied, in the Middle Ages, an important place in the political and religious landscape of the Lyon region. As other establishments, it took advantage of its peak to carry out ambitious projects aimed at protecting its interests and showing everyone its legitimacy and ambition. The reconstruction of its principal church, between the end of the 11th and the beginning of the 13th centuries, participated at this phenomenon like the redaction of its cartulary. This place of worship was monumental by its dimensions and by its architecture. It was plundered then almost completely destroyed during the years that followed the French revolution. It was neglected for a long time by the scholars who were not interested in a church impossible to locate in the village. Some recent and multidisciplinary researches have nevertheless uncovered archaeological, historical and liturgical documentation that was almost unknown and very little used. It is now possible to write the history of this church, over the long term, but also to try to restore its medieval state.